The Impact of Organizational Health and The Levels of Transformational Leadership of School Teachers in Indonesia: A Systematic Review - Priyoherianto, Andri; Mustaji, Mustaji; Roesminingsih, Erny; Hariyati, Nunuk; Rianto, Yatim; Khamidi, Amrozi (Indonesia Emerging Literacy Education, 2025)
Objective: The primary goal of this review is to investigate the connection between organizational health and transformational leadership in the context of school leadership practices. The qualities of transformational leadership and how it is developed from different foundational leadership theories are also intended to be examined in this review. Method: The type of research used is Research and Development (RnD). Results: Following the filtering process, 34 papers were selected for examination using a variety of pre-established criteria as part of the systematic review approach. According to this systematic review, a relationship exists between the organizational health components proposed by Hoy and Miskel and the transformational leadership features presented by Bass. This is crucial since it serves as the foundation for this study. Novelty: The components of organizational health—namely integrity within institutions, collegial leadership, teacher relationships, and academic emphasis—play a pivotal role in shaping effective school environments. These elements are closely aligned with the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Understanding the interplay between organizational health and transformational leadership provides valuable insight into how school leaders can foster positive, sustainable change.